If you're reading this, it's too late - Bosch, Pseudonymous; Ford, Gilbert (New York : Little Brown & Co., 2009)
Cass and Max-Ernest discover the Museum of Magic, unscramble more coded messages, and solve new mysteries in their attempt to thwart the Terces Society's ambitions of discovering immortality.
Sequel to: The name of this book is secret.
760
Accelerated Reader AR
Keywords: Magic tricks -- Juvenile fiction; Adventure stories; Immortality -- Juvenile fiction; Magic tricks -- Fiction; Adventure and adventurers -- Fiction; Immortality -- Fiction